The Control System Modeling and The Mechanical Structure Analysis For EMCVT - Lei ZHANG; Xiaomei CONG; Hujian Pan; Zuge CAI; Xiumin YANG (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The current automotive metallic belt continuously variable transmission (CVT) mostly use hydraulic system to push the cone disc and achieve the speed ratio control. A new Electrical Mechanical Continuously Variable Transmission without hydraulic control (Electrical Mechanical CVT, EMCVT) studied in this paper, uses the rolling screw mechanism to press cone disc, achieves speed regulation through the electronic control mechanism, and abandons the energy-intensive hydraulic system. In this paper, based on the analysis of mechanical configuration, the EMCVT's transmission system and its speed regulation process, speed ratio control characteristic and the clamping force control feature are studied and modeled. Besides, the Control strategy of the transmission system driven by motor is built, so as to provide an important theoretical basis for the further building of EMVCT's control system and the selection and implementation of Control strategy. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2935